Environmental Enrichment During Adulthood Reduces Sucrose Binge-Like Intake in a High Drinking in the Dark Phenotype (HD) in C57BL/6J Mice - Rodríguez-Ortega, Elisa; Alcaraz-Iborra, Manuel; de la Fuente, Leticia; de Amo, Enedina; Cubero, Inmaculada (Frontiers in Behavioral Neuroscience, 2019)
Repetitive binge episodes favor transition to binge-eating disorders. Experimental evidence points to positive effects of environmental enrichment (EE) on drug/food addiction, although little is known regarding EE modulation of binge-like consumption. Here, we evaluate the following: 1) whether switching from nonenriched (SE) to enriched environmental (EE) housing conditions during adulthood alters a stable pattern of voluntary sucrose (10% w/v) binge-like intake in high (HD) vs low (LD) drinking phenotypes under a drinking in the dark (DID) schedule; and 2) sucrose binge-like intake in a DID task in response to a pharmacological challenge with an OXr1 antagonist in HD/LD subpopulations after long-term exposure to SE or EE conditions. Adolescent (postnatal day 21; PND21) mice were housed in SE conditions. At PND65, all animals were long-term exposed to sucrose DID. On the first episode of DID (PND65), animals were divided into HD vs LD subpopulations according to their sucrose intake. On PND85, an OXr1 antagonist test was conducted on HD and LD mice with SB-334867 (SB) administration. On PND95, HD and LD subpopulations were again randomly allocated into two subgroups, finally leading to four experimental conditions: HD-SE, HD-EE, LD-SE and LD-EE. Sucrose binge-like intake continued until PND116, when a second SB test was conducted. The main findings are 1) a single 2 h episode of sucrose binge drinking in a DID procedure consistently segregates two behavioral subpopulations, HD and LD; 2) when adult mice reared in SE conditions and long-term exposed to sucrose DID were switched to EE conditions, an immediate reduction in sucrose binge-like intake was observed in HD mice, suggesting a therapeutic role of EE exposure; and 3) administration of the OXr1 antagonist caused an acute reduction in sucrose binge-like intake in HD and LD mice exposed to SE conditions. Importantly, exposure to EE conditions blunted the inhibitory effect of SB on sucrose binge consumption in both behavioral phenotypes, indirectly suggesting an impact of EE on OXr1 signaling. We propose the working hypothesis that EE might regulate OX-dependent anxiety/compulsivity brain systems, which in turn might secondarily modulate sucrose binge-like intake.